Production of in vitro embryos in vitro a portable carbon dioxide incubator and viability in vivo post transfer to recipients cows - Pérez Durand, Manuel Guido (2019)
The objective was to determine the addition of 5% carbon dioxide (CO2) from effervescent granules or gasified to a portable incubator (taper) to evaluate the in vitro production of embryos of oocytes aspirated from ovaries of cows slaughtered in the slaughterhouse and evaluate viability in vivo through pregnancy in recipient cows. As a portable incubator, a 500 cm3 plastic taper was used, to which a valve for controlling the addition of CO2 was conditioned. The maturation was carried out for 24 h, fertilization for 18 h and embryo culture for 7 d in 500 uL of the media in petry plates and introduced into the portable incubator, which was placed in a water bath at 38.5 ° C. At 72 h post fertilization the proportion of zygotes was determined, at 7 d post culture the embryos were counted. The fertilization results with the addition of CO2 from effervescent granules was 38.28% (103/269), with the addition of gasified CO2 37.24% (146/392) and control 49.82% (144/289) (p<0.05); for embryo production it was 18.95% (51/269), 19.38% (76/392) and 24.56% (71/289), respectively (p>0.05); the pregnancy rate in recipient cows was 38.46% (5/13). In conclusion, it is possible to produce in vitro embryos of cattle, using a portable CO2 incubator at field level.